Fuzzy Difference Operators for Spatial Change Detection in 2D Spatial Scene - Nadeem Salamat; El-hadi Zahzah (Cybergeo, 2011)
Fuzzy difference operators are used in different fields of decision making processes, image analysis and computer vision applications. Change detection in a spatial scene is the basic issue in modeling relative motion between object pair. Many approaches are adopted to change detection in a spatial scene and change in spatial relations is one of them. Separate methodologies are adapted to determine the change in topological, directional and distance relations. In this paper, a methodology for detection of a spatial change based on fuzzy matrix calculus is presented. Difference of combined fuzzy topological and directional relations matrices is determined by fuzzy difference operators. Experiments are performed to validate the proposed method and the promising results are obtained.